A typical presentation of viral encephalitis with psychiatric manifestation and quick; complete recovery - Shrestha, Dhan Bahadur; Panta, Chiranjibi; Rawal, Namrata; Bhandari, Paawan; Manandhar, Pradeep; Katuwal, Nagendra (Journal of Chitwan Medical College, 2018)
Viral Encephalitis is a common emergency condition, among the virus herpes simplex is on the top. Encephalitis usually present with clinical features of fever, headache, confusion with seizures but presentation can be atypical making the situation difficult and needs crucial judgement. Here we present an atypical case of viral encephalitis in a 32 years old male, initially presented with feature of depression with concomitant elicited history of conflict in the family confounding the situation. The case was managed successfully with multidisciplinary approach involving psychiatrist, neuro physician, and neurosurgeons in hospital for one month.